Verdet constant of various types of honey and sugar solution analyzed at different concentration. Issue 1 (February 2021) - Purwandari, E; Misto,; Hidayat, R; Supriyadi,; Cahyono, B E
Abstract: The optical activity effect of material on the polarization of a light beam due to the external magnetic field has observed through Faraday rotation. The use of the Verdet constant represents the behaviour characteristic of the material. This paper had reported the Verdet constant of some honey types compared with a sugar solution that was analyzed at different concentrations. Laser He-Ne had been used to observe the change of its polarization angle (Faraday rotation) when the external magnetic field applied at 50 gauss, 100 gauss, and 150 gauss. They were produced by a solenoid wrapped around the sample container, connected to the DC power supply. The Verdet constants of Kaliandra honey, Randhu honey, and Pahit honey, respectively, indicate their dependence on concentration. The profile of concentration dependence of the Verdet constant for all three types of honey is the same as that of the sugar solution. However, the highest Verdet constant is achieved by Kaliandra honey when analysed at a concentration of 30%.